Simulasi Karakteristik Proses Pembakaran pada Motor Bensin 3000 cc - Rosid Rosid; Viktor Naubnome (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2017)
Research conducted through the development of a simulation model of the combustion process in the combustion parameters using 3000 cc petrol engine with combustion models correspond to the experimental approach. The purpose of the study by simulations that include combustion and emissions formation in the combustion chamber. The simulation was performed by varying the rotation of 1000 rpm, 1500 rpm, 2500 rpm, 3500 rpm and 4500 rpm, to determine the most optimal working areas at 3000 cc petrol engine. The simulation results show the most optimal working range at 3500 rpm combustion, the fuel starts burning at a pressure of 2318.40 kPa at temperatures of 722.25 K and a crank angle of 716 degrees. The lowest peak pressure 2643.00 kPa at 748.75 crank angle degrees, the highest peak pressure of 4097.80 kPa at 742.25 crank angle degrees. Lowest peak temperature 1954.73 776.50 K at the crank angle degrees, the highest peak temperature 2173.51 755.75 K at the crank angle degrees. Changes of the lower peak pressure to the highest peak pressure ranges from 64.5%, while the lowest peak temperature change to the highest peak temperature ranges from 89.9%.